The Effectiveness of Simak-Bmn Application on Financial Statement Quality in Terms of Training, Peer Advice Ties and Users Satisfaction (Case Study In A-Non-Departmental Public Bodies) (International Conference of Graduate School on Sustainability (ICGSS), 2021)
This study aimed to analyze the effectiveness of SIMAK-BMN on Financial Statement Quality in terms of Training, Peer Advice Ties and Users Satisfaction. Data collection is carried out using questionnaires. The respondent in this study are 35 users of SIMAK-BMN in A Non-Departmental Public Bodies. This study uses the likert scale using SPSS. Data processing in this study, using a multiple regression analysis. The result shows the application of SIMAK-BMN which is measured by training, peer advice ties and satisfaction of users have a positive effect on quality of financial statement.